Complexing Behaviour of Some Schiff Bases with Co(II), Ni(II) and Cu(II) - Rai, B.K. (Asian Journal of Chemistry, 2010)
A series of homobinuclear metal complexes of the type [M(HL1-2)2X2] where M = Co(II), Ni(II) and Cu(II); HL1= 2-(3´,4´-dimethyl) phenyl imino-3-hydroxy butane; HL2 = 2-(3´,5´-dimethyl) phenyl-imino-3-hydroxy butane; X = Cl–, Br–, I–, NO–3 and ClO–4 have been synthesized and characterised on the basis of elemental analysis, magnetic susceptibility, conductivity measurements, infrared and electronic spectral data.